Leakage analysis and ground tests of knife edge indium seal to lunar sample return devices. (May 2019) - Zhang, Bin; Hong, Haocen; Yu, Min; Yang, Huayong
This work deals with the lunar sample return project, which requires lunar samples to be returned back to the ground without contamination. In this paper, a knife edge indium seal is proposed as a primary sealing form, where indium–silver alloy is welded into an annular groove of a cylindrical container firstly and then extruded by an annular knife edge of a cylindrical lid. The analysis of the leakage and sealing reliability of knife edge indium seal is the main aim of this paper. Firstly, the pretreatment of knife edge indium seal is discussed. Key techniques on indium welding are studied to evaluate its sealing reliability, with the tensile strength and welding void ratio mainly being discussed. Secondly, by means of "Roth" leakage theory, mathematical models on the leak rate for knife edge seal are established. By means of the finite element analysis, the knife edge geometry is optimized with minimum pressing force required. The results justify that the knife edge seal demands much lower pressing force to achieve a considerable sealing performance, which is suitable for low-powered operation. Finally, the ground tests are carried out to evaluate the feasibility of the indium welding and to measure the leak rate of the knife edge indium seal. Experimental results demonstrate the indium welding onto the stainless steel container is feasible, and the leak rate at room temperature is 3.0 × 10 −10 Pa·m 3 /s, which is much lower than the rubber O-type ring seal. The knife edge indium seal is suitable for lunar sample return devices.